Metaphysical Foundation of Bekwarra Epistemology: A Study of An Indigenous Knowledge System in Cross River State, Nigeria (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
The dominant discourse in Western epistemology has long proceeded on the assumption that knowledge claims can be isolated from metaphysical commitments. This paper challenges that assumption by examining the metaphysical foundations of knowledge among the Bekwarra people of northern Cross River State, Nigeria. The Bekwarra, a minority ethnic group with a population estimated at approximately 150,000, possess a distinctive worldview that has been understudied in African philosophy. Drawing on primary ethnographic sources, oral traditions, and existing scholarship, the study demonstrates that Bekwarra epistemology is inextricably grounded in a distinctive metaphysical framework characterised by three irreducible strands: creative determinism rooted in the supreme deity Okah and the progenitor Agba; reactive interference mediated by spiritual entities such as Nndum and the Igbatorobi cult; and representativeness expressed through naming practices, nicknames, and the Agwunihe philosophy of land ownership. The paper argues that these metaphysical commitments are not pre logical or proto scientific but constitute a coherent, internally consistent system that generates genuine knowledge. This has profound implications for cross cultural philosophy, for it suggests that what counts as knowledge in any tradition is shaped by what that tradition takes reality to be. The paper concludes that a truly global epistemology must take seriously the metaphysical diversity of human thought and cannot privilege a putatively neutral, disembedded conception of rationality.